Emissão de poluentes atmosféricos por automóveis no Brasil, 2010-2020: uma revisão de literatura - COUTINHO, Samuel Leal (2022)
Considering its impact on human health, ecosystems and the quality of construction products, air pollution has been one of the main topics of concern for the scientific community, which considers it a fundamental dimension in the pursuit of sustainable development. Brazilian legislation guides the creation and implementation of a national air quality plan with the objective of keeping emissions within acceptable limits. Emissions inventories can be used to study an area's gas emissions over a period. With it, the sources of emissions can be identified, leading to air quality control strategies. In this sense, this work sought to collect data from studies of vehicle emissions, by cars only, of three pollutants: carbon monoxide, particulate matter and sulfur dioxide in the years 2010 to 2020. For this, a systematic literature search was carried out resulting in 43 works for analysis. It was found that there was a reduction in emissions in the analyzed period, but even so, values higher than the ideal ones. Carbon monoxide was the most pollutant emitted by automobiles. Sulfur dioxide was the pollutant that most reduced its emissions, largely due to advances in technology in the manufacture of fuels. Future research requires improved measures to reduce air pollution from vehicles, as well as government proposals to control emissions. Therefore, this work will contribute with new vehicular emissions inventories for the temporal and spatial comparison of these emissions, in order to create intervention proposals that contribute to environmental preservation.